Implementation of Duvet Covers in Rooms at the Grand Antares Hotel Medan Indonesia - Angin, Fitri Yolanda Br Perangin (Cattleya Darmaya Fortuna, 2023)
A duvet cover is a fabric casing used to encase a blanket or comforter, providing both protection and warmth. In the hotel industry, the correct implementation of a duvet cover by room attendants requires specific skills, accuracy, and neatness. This research aims to examine the procedures of duvet cover implementation in guest rooms, assess the skills of room attendants, and evaluate the supervisory role in maintaining standard practices at the Swiss-Belinn Hotel Medan. The study utilized a qualitative descriptive method, involving direct observation and interviews with eight respondents, including room attendants, supervisors, and the Assistant Executive Housekeeper. The findings indicate that the application of duvet covers by room attendants is often suboptimal, characterized by untidy work and a lack of adherence to standard operating procedures. Furthermore, insufficient supervision and the absence of regular training contribute to the inconsistent quality of bed arrangement. It is recommended that the hotel management provide structured training and continuous performance monitoring to improve the room attendants' skills and ensure the proper implementation of duvet covers in accordance with professional housekeeping standards.